EC155 – physical handcrafted model for Gading Group Berhad / Zaidi Yusoff and Ahmad Adam Zakaria - Yusoff, Zaidi; Zakaria, Ahmad Adam (Faculty of Art and Design, 2021)
The production of Gading Group Berhad's EC155 helicopter model is an example of handcrafted model that requires high level skill and creativity. This model was made from polyvinyl chloride hardboards or known as PVC boards. PVC boards were chosen because they have desirable properties such as lightweight, flexibility, smooth surface, durability, and resistance to moisture, corrosion, vibration, noise, moths, and heat. PVC boards, in addition to being easily modified to achieve the desired shape and color, are easily fabricated and handled, allowing modelers to put up any structure that meets the required model making design or prototype that follows the designers' and modeler’s requirements and aspirations. Because of these advantageous properties, PVC foam boards are used in interior design, such as furniture, buildings, and advertising, in addition to industrial design. This is the first step to construct on how to build up the model before the modeler starts with other parts. The modeler needs to understand and explore how the PVC board can be transformed from flat board to become rounded or oval by using their creativity and exploration of the board's behavior’. Once the board is in the right structure so the modeler can set up to cover the structure with the pieces of PVC board before the model can be forward to the next step. It’s difficult to construct the structure if we don’t have any guidance like a blueprint or technical drawing of the project.